Prototype of a marine animal sculpture from plastic waste: Role in promoting the image of Thai tourism - Donprasri, Surachai (Humanities, Arts and Social Sciences Studies, 2025)
Plastic waste poses a significant threat to communities and the environment. Urban waste overflow is a direct consequence of large-scale economic, social, and industrial expansion that prioritizes the mass production of plastics for everyday use. This has led to an accumulation of plastic waste that is difficult to dispose of and has contributed to the endangerment of marine species such as sea turtles, dolphins, whales, and dugongs. Moreover, plastic pollution has caused ecological degradation due to the contamination of microplastics, which pose risks to human health and negatively impact Thailand's tourism industry. This paper aims to design and create a prototype of a marine animal sculpture made from plastic waste for installation at Cha-am Beach, Phetchaburi Province. The objectives of this study are to create and evaluate a prototype of a marine animal sculpture made from plastic waste, assess tourists' awareness of responsible tourism through viewing the sculpture illuminated with nighttime lighting, and promote tourism and environmental awareness. This research incorporates the simulacra consumption theory and reviews relevant literature on art, particularly focusing on plastic whale sculptures. It is hoped that this creative artwork will enhance Thailand's tourism image and raise awareness among tourists about the issue of marine plastic pollution, which has led to ecological degradation due to microplastic contamination and has negatively impacted the tourism industry.